Relationship between peak oxygen uptake and regional body composition in Japanese subjects - Kanae Oda; Nobuyuki Miyatake; Noriko Sakano; Takeshi Saito; Motohiko Miyachi; Izumi Tabata; Takeyuki Numata (Journal of Sport and Health Science, 2014)
Purpose: To investigate the link between peak oxygen uptake and regional body composition by dual energy X-ray absorptiometry (DEXA) in Japanese subjects. Methods: A total of 93 men (42.2 ± 12.3 years old) and 106 women (43.5 ± 12.3 years old) were enrolled in this cross-sectional investigation study. Peak oxygen uptake was measured by the breath-by-breath method. Regional body composition i.e., body fat mass, lean body mass, and body fat percentage was evaluated using DEXA. In addition, metabolic risk parameters were also evaluated. Results: Peak oxygen uptake was 37.6 ± 8.7 mL/kg/min in men and 31.1 ± 6.4 mL/kg/min in women, and decreased with age in both genders. Peak oxygen uptake was significantly correlated with total body fat percentage (men: r = −0.684, p < 0.0001; women: r = −0.681, p < 0.0001). These associations remained even after adjusting for age and total lean body mass. However, peak work rate was positively and significantly correlated with leg lean body mass. Conclusion: Peak oxygen uptake was closely correlated with total body fat percentage in both genders. Aerobic exercise as well as leg resistance training might be useful for improving peak oxygen uptake in Japanese subjects.